The Transformation of Ronggeng Dukuh Paruk - Oki Edi Purwoko (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2017)
Two main Things is analyzed in this study, The first is the view of the trilogy, when its exotication much symbolized by Srintil and Dukuh Paruk was viewed in complex, divine and yet paradoxal object. This analysis was coming from the study of the genre which flourished in Indonesian literary on 70’s and 80’s, also from the political sociological perspectives when rapid development triumphed the rational masculinity over irrational superstitious during 1980’s New order era.The second is the view of the trilogy when it was filmed in 2011 entitled Sang Penari. To be a more suitable with audience, the exotication including the life of Ronggeng is made to be a more pop icon than its complexity. The study was using the the arguments of orientalism and using the illustration of mainstream pop culture audience in Indonesia after the reformation era in 1998. The broader objectives of the study, is to give a deeper understanding to many pop culture artifacts in Indonesia, in terms of formation, pattern and type of communication. This study is more in interpretive path comparing several books and writings.